(untitled) (Communications in Computational Physics, 2010)
In this article we report the release of a new program for calculating emissivity and other physical parameters in atomic transition processes. The program, which can be downloaded with its documentation and a sample of input and output files from www.scienceware.net/id1.html, passed various rigorous tests and was used alongside R-matrix and Autostructure codes to generate theoretical data and analyze observational data. It is particularly useful for investigating atomic transition lines in astronomical context as the program is capable of generating a huge amount of theoretical data and comparing it to observational line list. A number of atomic transition algorithms and analytical techniques are implemented within the program and can be very useful in various situations. The program can be described as fast and efficient. Moreover, it requires modest computational resources.